1990
DOI: 10.1111/j.1476-5381.1990.tb12704.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of galanin, its analogues and fragments on rat isolated fundus strips

Abstract: 1 Rat and porcine galanin (rGal and pGal) produced dose-dependent contraction of rat fundus strips in a concentration range of 6 nM-100 nm. 2 The stimulatory effect of rGal on rat fundus strips was not modified in the presence of somatostatin (250nM), naloxone (1 uM), guanethidine (10 CM), a mixture of propranolol (3 #M) and phentolamine (3puM), tetrodotoxin (1 pM), indomethacin (10pM), atropine (1 M), a mixture of methysergide (2.5,UM) and ketanserin (2.5 uM), a mixture of mepyramine (10,UM) and cimetidine (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 26 publications
3
22
0
Order By: Relevance
“…Interestingly, nonamidated and amidated hGals showed no differences in biological activity or high-affinity binding (results not shown). These findings are in agreement with several structure-activity studies for the characterization of Gal and the interaction with its receptor: it has been demonstrated that the N-terminal portion ofGal, which is completely conserved in all species, is important for receptor interaction in rat pancreatic B cells (21,34), central nervous system neurons (35,36), and isolated smooth muscle strips (14,29). In contrast, a number of Gal-specific antisera reacting with the C-terminal part of the peptide show poor cross-reactivity among species and divergent tissue levels of Gal (4, 6).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Interestingly, nonamidated and amidated hGals showed no differences in biological activity or high-affinity binding (results not shown). These findings are in agreement with several structure-activity studies for the characterization of Gal and the interaction with its receptor: it has been demonstrated that the N-terminal portion ofGal, which is completely conserved in all species, is important for receptor interaction in rat pancreatic B cells (21,34), central nervous system neurons (35,36), and isolated smooth muscle strips (14,29). In contrast, a number of Gal-specific antisera reacting with the C-terminal part of the peptide show poor cross-reactivity among species and divergent tissue levels of Gal (4, 6).…”
Section: Discussionsupporting
confidence: 91%
“…In comparison to bovine Gal (bGal) and rGal, 7 and 4 residues are different, respectively. All amino acid substitutions are restricted to the C-terminal part of the molecule (positions [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Table 1 compares the sequences of hGal, rGal, pGal, and bGal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of galanin are mediated by three distinct G-protein-coupled receptors that involve different signaling pathways: galanin receptor 1 (GalR1) (G i/o ), GalR2 (G q/11 ) and GalR3 (G i/o ) (Smith et al, 1997;Branchek et al, 1998Branchek et al, , 2000Wang et al, 1998). The effect of galanin on gastrointestinal motility varies according to the species and the segment investigated, suggesting activation of multiple receptors (Tamura et al, 1987;Muramatsu and Yanaihara, 1988;Fontaine and Lebrun, 1989;Katsoulis et al, 1990). To better understand which receptor mediates a particular galanin effect, it is critical to determine the tissue specific distribution of individual GalRs.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of galanin on gastrointestinal motility are both stimulatory and inhibitory, and are the result of a direct myogenic and a nerve-mediated effect involving the release of other transmitters. In general, galanin actions vary depending on the tissue, the species and the experimental conditions [8,12,16,25].…”
Section: Introductionmentioning
confidence: 99%